Generalized and tissue specific glucocorticoid resistance. (15th June 2021) - Martins, Clarissa Silva; de Castro, Margaret
Abstract: Glucocorticoids (GCs) are steroid hormones that influence several physiologic functions and are among the most frequently prescribed drugs worldwide. Resistance to GCs has been observed in the context of the familial generalized GC resistance (Chrousos' syndrome) or tissue specific GC resistance in chronic inflammatory states. In this review, we have summarized the major factors that influence individual glucocorticoid sensitivity/resistance. The fine-tuning of GC action is determined in a tissue-specific fashion that includes the combination of different GC receptor promoters, translation initiation sites, splice isoforms, interacting proteins, post-translational modifications, and alternative mechanisms of signal transduction. Highligths: Glucocorticoid resistance may be familial or acquired, partial or complete, generalized or tissue-specific. Acquired tissue-specific glucocorticoid resistance has been mainly observed in the context of chronic inflammatory states. Polymorphisms in the NR3C1 gene may influence glucocorticoid sensitivity. NR3C1 mutations have been described in patients with familial generalized glucocorticoid resistance (Chrousos' Syndrome).